Autuações fiscais federais e gerenciamento de resultados no Brasil - Vaz, Urias Otaviano (2023)
The objective of this study is to examine whether earnings management increase when there is an increase in federal tax fines (quantity and values) in economic sectors. The quantity and the values of tax fines issued annually, by economic sector, by the Receita Federal do Brasil (RFB), are made available in the annual oversight reports by the federal agency. The unbalanced sample is made up of 3,168 observations, from 349 companies listed on Brasil, Bolsa, Balcão S.A. [B³], between the years 2012 and 2021. The earnings management models used in this study include practices via discretionary accruals and via real activities. To date, no studies have been found that investigate the incentives for earnings management practices arising from economic sectors, according to the information provided by the RFB in its annual Reports, nor that carry out an analysis of possible relationships between variations in tax fines in Brazilian companies. Using the TOBIT estimator, after estimating earnings manipulation proxies, and classifying the companies in the sample as they appear in the economic sectors applied by the RFB, it was possible to find evidence of earnings management, whether via discretionary accruals or via real activities. Finally, it was found that in the positive variation in the quantity of oversight, there was a tendency to earnings manage through discretionary accruals, but when the increase variation was in oversight values, there were more results with significance in real activities.